PENGGUNAAN KOLASE KALIGRAFI DALAM PERKEMBANGAN KREATIVITAS ANAK USIA 5-6 TAHUN - Sunia Susilawati; Kurnia Akbar (Ash-Shobiy: Jurnal Pendidikan Islam Anak Usia Dini dan Al-Qur'an, 2023)
The development of creativity is an ability that reflects, flexibility, and originality in thinking as well as the ability to develop thoughts and activities. The natural creativity of an early childhood can be seen from his/her great curiosity. This can be seen from the learning activities they can do at school or at home. The purpose of this study is to determine whether the use of calligraphy collages can develop the creativity of children aged 5-6 years at TKIT Nurul Amal Pondok Cabe Illir Tangerang Selatan.In this study, the authors used descriptive qualitative research by collecting research data through observation, interview instruments and documentation. The research subjects are principals, classroom teachers and parents. While the object of this research is the application of calligraphy collages to the creativity development of children aged 5-6 years at TKIT Nurul Amal Pondok Cabe Illir, South Tangerang.The results obtained from observational research are the development of children's creativity in the application of calligraphy collages, children are happy and enthusiastic in participating in calligraphy collage learning, because with the application of calligraphy collages children play an active role in the learning process.